Improving performance of external resources for IT services of company BCD - DeGracia, Marvin (Animo Repository, 2023)
Information Technology (IT) services outsourcing has been a long practice in several industries across the globe. Many companies see this as a strategic approach to reduce operational costs and achieve competitive advantage. However, this approach does not fully guarantee these benefits as challenges may arise before, during, and after deciding to go with this strategy. In this action research, we aim to address the challenges of one team who offers IT services outsourcing to Company BCD. This team, called Application Support Group (ASG), has been highlighted several times in performance reviews because of their poor performance. Given this situation, Company BCD is not receiving the expected returns of its investment to ASG. Together with my collaborators, we aim to improve the overall performance of ASG so that Company BCD can fully maximize the potential benefits of investing in IT services outsourcing. We focused on addressing three main issues that manifested: 1) unnecessary escalations, 2) non-compliance with standard operating procedures, and 3) communication issues. By reviewing related literature, applying frameworks, and focusing on these three main issues, the research team was able to come up and implement actions the helped in driving the performance of ASG. Overall, driving the performance of external IT resource of Company BCD required revisiting roles and responsibilities, team structure, workflows, and collaboration with different levels of management. This action research concluded that our goal of addressing the three main issues basically boils down to achieving operational excellence. To achieve this, there are processes and foundational elements that are necessary to be in place.